Low frequency oscillations in wind and circulation fields over India during northern summer monsoon - CHOWDHURY, A.; MUKHOPADHYAY , R.K.; RAY, K.C. SINHA (MAUSAM, 1990)
The study presents result of low frequency oscillations in zonal and meridional wind and divergence and vorticity fields during summer monsoon over India. Harmonic analysis has been adopted for this purpose to detect prominent periodicities; Strength of Hadley circulation has been related to the monsoon rainfall. Inter-annual fluctuations in the oscillations have been examined with the help of Homelier diagrams. The contribution of Kelvin and Rossby waves in the excitation of the oscillations has been discussed. Role of easterly and westerly anomalies in the establishment of the monsoon and the active-break cycles has been projected. The vertical structure of the cycles has been investigated and plausible explanation offered, particularly on its tilt and its relation to monsoon activity. Possible mechanism on generation. Propagation, Intensification and weakening of the oscillations over Indian latitudes has been proposed.